The flavor of UV physics - Bruggisser, Sebastian; Schäfer, Ruth; Dyk, Danny van; Westhoff, Susanne (Journal of high energy physics, 2021)
New physics not far above the TeV scale should leave a pattern of virtual effects in observables at lower energies. What do these effects tell us about the flavor structure of a UV theory? Within the framework of the Standard Model Effective Field Theory (SMEFT), we resolve the flavor structure of the Wilson coefficients in a combined analysis of top-quark and B-physics observables. We assume that the Yukawa couplings are the only sources of flavor symmetry breaking, a framework known as Minimal Flavor Violation. Our fits to LHC and b-factory measurements show that combining top and bottom observables is crucial to pin down possible sources of flavor breaking in a UV theory. This analysis includes the full analytic expansion of SMEFT coefficients in Minimal Flavor Violation and a detailed study of SMEFT effects in b → s flavor transitions.